The Eclipse of Sacramental Realism in the Age of Reform: Re-thinking Luther's Gutenberg Galaxy in a Post-Digital Age - Hoff, Johannes (New blackfriars, 2018)
In the last 500 years our modern world has oscillated between the belief in “disenchanted” strategies of bureaucratic control and surveillance, and the celebration of iconoclastic ruptures that are supposed to preserve our sense of freedom and dignity. Yet, the equilibrium between these poles has fallen out of balance after the turn of the millennium. While the obsession with control has released concerted efforts to replace our supposedly irrational intelligence by the “artificial intelligence” of digital technologies, the implementation of ICT technologies in our everyday life has undermined the iconoclastic conviction that artefacts are merely tools. Our smartphones have a “magic life” of their own – be it that they afford a life that we appreciate, or that they nudge us into a life that we abhor. This challenge requires us to recover our ability to distinguish between idolatrous attachments and the prudent use of “magic objects” that is consistent with our natural desire to transform our life for the better. The following essay will discuss the question to what extent the basic assumptions of the confessionalized religions of the post-Reformation era distract us from the task of engaging with this challenge. Moreover it will question the modern inclination to replace the engagement with sacramental objects with an engagement with pious “master signifiers”: authoritative substitutes for the “body of Christ”, like the Eucharistic host, the Bible or secular party books that reduce the attachment to religious traditions to a matter of formal belief and submission to an authoritative system of clerical, bureaucratic, or (today) robotic surveillance.